Mechanical circulatory support in ventricular arrhythmias - Tavazzi, Guido; Dammassa, Valentino; Colombo, Costanza Natalia Julia; Arbustini, Eloisa; Castelein, Thomas; Balik, Martin; Vandenbriele, Christophe (Frontiers in Cardiovascular Medicine, 2022)
In atrial and ventricular tachyarrhythmias, reduced time for ventricular filling and loss of atrial contribution lead to a significant reduction in cardiac output, resulting in cardiogenic shock. This may also occur during catheter ablation in 11% of overall procedures and is associated with increased mortality. Managing cardiogenic shock and (supra) ventricular arrhythmias is particularly challenging. Inotropic support may exacerbate tachyarrhythmias or accelerate heart rate; antiarrhythmic drugs often come with negative inotropic effects, and electrical reconversions may risk worsening circulatory failure or even cardiac arrest. The drop in native cardiac output during an arrhythmic storm can be partly covered by the insertion of percutaneous mechanical circulatory support (MCS) devices guaranteeing end-organ perfusion. This provides physicians a time window of stability to investigate the underlying cause of arrhythmia and allow proper therapeutic interventions (e.g., percutaneous coronary intervention and catheter ablation). Temporary MCS can be used in the case of overt hemodynamic decompensation or as a “preemptive strategy” to avoid circulatory instability during interventional cardiology procedures in high-risk patients. Despite the increasing use of MCS in cardiogenic shock and during catheter ablation procedures, the recommendation level is still low, considering the lack of large observational studies and randomized clinical trials. Therefore, the evidence on the timing and the kinds of MCS devices has also scarcely been investigated. In the current review, we discuss the available evidence in the literature and gaps in knowledge on the use of MCS devices in the setting of ventricular arrhythmias and arrhythmic storms, including a specific focus on pathophysiology and related therapies.